DNA replication in growth conditions that mimic the natural habitat of Haloferax volcanii - McCulloch, Bryn (2021)
The initial aim of the project was to assess origin-independent replication in Haloferax volcanii (Hfx. volcanii). DNA replication is initiated at specific sites on the chromosome called origins. Origins are assumed to be an essential feature of all cells, because they serve as binding sites for proteins that recruit the DNA replication machinery. In work published by Hawkins et al, (2013), it was demonstrated that mutants of Hfx. volcanii lacking all replication origins are viable; in fact, they grow faster than the wild-type and have no obvious cellular defects. By contrast, deletion of origins from Eukaryotes and Bacteria leads to cell death or profound growth defects.